2021
DOI: 10.3390/ijerph18168522
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Application for the Analysis of Stress Relief in the Seasonal Landscape

Abstract: This study proposes an integrated approach to assess the psychological and physiological responses of people in natural seasonal landscapes. The questionnaire of restoration outcomes scale (ROS), willingness to visit (WTV), cultural ecosystem services (CES) cognitive classification, and the neuroscientific technique based on electroencephalogram (EEG) measurements were applied. The effects of different landscapes on human perception were studied by comparing the EEG data of different landscape types and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The similarity with the classification of people’s emotions shows that different landscapes do cause subtle changes in people’s emotions. At the same time, it also proves that it is feasible to identify people’s perception of different landscapes through multi-dimensional EEG features [ 60 ]. This result is of great significance for evaluating the impact of landscapes on people, which also has important reference value for the quantification of ecosystem cultural services [ 44 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The similarity with the classification of people’s emotions shows that different landscapes do cause subtle changes in people’s emotions. At the same time, it also proves that it is feasible to identify people’s perception of different landscapes through multi-dimensional EEG features [ 60 ]. This result is of great significance for evaluating the impact of landscapes on people, which also has important reference value for the quantification of ecosystem cultural services [ 44 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the Yellow Ginkgo Scenic Forest was used after the T3 stage in the experiment. Some studies have shown that there is significant seasonality in the quantitative value of brain wave data [6].This seasonality can be more pronounced in environments with high-wavelength colors, such as yellow [30], and the brain function of the subjects is more active [31]. This may also explain the differences observed in the three time periods.…”
Section: Time Effect On Physiological Restorative Effectsmentioning
confidence: 97%
“…From a research perspective, in addition to time series (season, day and night), it also includes health feedback under dynamic changes in behavior sequences (behavior patterns, behavior types) and environmental type sequences (buildings, blue spaces, green spaces). Time dynamics research mainly focuses on the significant recovery effects of changes in plant, facility, human elements, or appearance over time on stress [5,6]. For example, Zhou, Y. found that green spaces in summer significantly promote physical activity compared to winter [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment noted a greater abundance of positive emotions provided by natural environments21. Wang and Xu (2021) employed EEG technology and surveys to assess psychological and physiological responses to seasonal landscapes. The experiment revealed signi cant differences between winter and summer landscapes, with only winter landscapes showing signi cant gender differences.…”
mentioning
confidence: 99%